Method for manufacturing film, and porous film

JP2024001721A5Active Publication Date: 2025-03-13KAO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022100569
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-06-22
Publication Date
2025-03-13
Estimated Expiration
2042-06-22

AI Technical Summary

Technical Problem

Porous films used in absorbent articles face issues with shrinkage due to polymer chain reorientation during winding, leading to film sticking and article warping, especially in flexible films.

Method used

A method involving two-stage heat treatment and controlled stretching with specific temperature and speed conditions to relax polymer chain orientation, followed by immediate second heat treatment before winding, to produce a film with reduced shrinkage and enhanced dimensional stability.

Benefits of technology

The method effectively suppresses film shrinkage, ensuring stable winding and preventing article warping, with a heat shrinkage rate of 8% or less in the machine direction and improved flexibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To suppress shrinkage of a film manufactured through a stretching step due to orientational relaxation of high molecular chains.SOLUTION: A method for manufacturing a film has the steps of: extruding a molten resin from a die to form it into a film extending in one direction; stretching the film obtained by the film formation, in a lengthwise direction while conveying it; applying a first heat-treatment to the stretched film while conveying it; and winding the film after the heat-treatment. Immediately before winding the film after the heat-treatment, the film is applied with a second heat-treatment.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a film.The present invention also relates to a porous film. [Background technology]

[0002] Porous films are often used as backsheets in absorbent articles such as disposable diapers, sanitary napkins, etc. Absorbent articles equipped with a backsheet made of a porous film have the advantage that moisture generated from the wearer's body when worn is easily released to the outside through the backsheet, making it difficult for the wearer to become stuffy when worn.

[0003] A commonly known method for producing a porous film involves melting a resin composition containing a thermoplastic resin and an inorganic filler, extruding the molten material through a die to form a film, stretching the film to generate a large number of micropores in the film, then subjecting the film to a heat treatment and winding it into a roll (see Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 10-110052 [Patent Document 2] JP 2000-001557 A Summary of the Invention [Problem to be solved by the invention]

[0005] In the above-mentioned method, the polymer chains of the resin constituting the film are stretched in one direction and oriented by stretching the film. The molecular orientation of the oriented polymer chains is relaxed by the subsequent heat treatment, and the crystal structure is stabilized. However, depending on the type of resin, the orientation of the polymer chains may occur again due to the tension applied in the winding process after the heat treatment, and the film may shrink when the orientation relaxes over a long period of time. When such a film is in a wound state, the film may become tightly wound as the film shrinks, and the films may stick to each other and the film may not be able to be unwound. In addition, when such a film is incorporated into an absorbent article, the absorbent article may warp due to the film shrinking over a long period of time, and the absorbent article may not be able to perform as expected. This phenomenon is particularly noticeable in flexible films that are easily deformed by small tension. Therefore, an object of the present invention is to provide a method for producing a film in which the orientation of polymer chains caused by stretching is alleviated, and a porous film. [Means for solving the problem]

[0006] In the present invention, a molten resin is extruded through a die to form a film extending in one direction, The film obtained by the film formation is stretched in the longitudinal direction while being transported, The stretched film is subjected to a first heat treatment while being transported; A film manufacturing method comprising a step of winding up the heat-treated film, The present invention provides a method for producing a film, in which the heat-treated film is subjected to a second heat treatment immediately before being wound up.

[0007] The present invention also relates to a composition for producing an olefin-based resin composition, the composition comprising an inorganic filler in an amount of 50 parts by mass or more and 400 parts by mass or less per 100 parts by mass of the olefin-based resin composition, The olefin resin composition contains a low-melting-point olefin resin having a melting point of less than 90° C. The degree of deformation in the machine direction is 0.060 N / (mm·(g / m 2 )) is less than or equal to The present invention provides a porous film having a heat shrinkage rate of 8% or less in the machine direction. Effect of the Invention

[0008] According to the present invention, it is possible to suppress shrinkage of a film produced through a stretching step due to relaxation of the orientation of polymer chains. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic diagram showing one embodiment of a film production apparatus used in the method of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described below based on its preferred embodiments with reference to the drawings. FIG. 1 shows a schematic diagram of one embodiment of a film manufacturing apparatus used in the method of the present invention. The apparatus 10 shown in the figure has a melt-kneading section 20, a forming section 30, a stretching section 40, a first heat treatment section 50, a cooling section 60, a slit section 70, a second heat treatment section 80, and a winding section 90 along the conveying direction. Each section of the apparatus 10 will be described below.

[0011] The melt-kneading section 20 has an extruder 22. The extruder 22 has a normal structure and is provided with a screw (not shown) in a cylinder (not shown). The extruder 22 has a hopper 21 for supplying the resin composition that is the raw material of the film. The extruder 22 further has a metering pump 23 at its tip for discharging the molten resin composition. The molten material discharged from the metering pump 23 passes through a filter 24 to remove foreign matter, and is then sent to the molding section 30.

[0012] The forming section 30 is provided with a die 31. As the die 31, those commonly used in the film manufacturing in the relevant technical field can be used without particular limitation. Typically, a T-die can be used. However, it is not limited to using a T-die, and other dies, such as a circular die used in the inflation method, can also be used. In the case of a T-die, on the downstream side of the die 31, an air chamber (not shown) and a film-forming roll 32a are installed in pairs to solidify the film formed by the die 31 and adjust its form, or as shown in FIG. 1, a pair of film-forming rolls 32a and a nip roll 32b are installed in pairs. Among these, when using the air chamber and the film-forming roll 32a, the air outlet of the air chamber is arranged parallel to the rotation axis of the film-forming roll 32a. On the other hand, when using the film-forming roll 32a and the nip roll 32b, their rotation axes are arranged parallel to each other and their peripheral surfaces are arranged to be in contact. From the perspective that forming defects such as surging are less likely to occur during the solidification of the film and the adjustment of its form, it is preferable that the air chamber and the film-forming roll 32a are installed in pairs.

[0013] The stretching section 40 is provided with a roll stretching machine. The roll stretching machine is provided with a pair of nip rolls 41a, 41b and another pair of nip rolls 42a, 42b located downstream of the nip rolls. When the peripheral speed of the pair of nip rolls 41a, 41b is V1 and the peripheral speed of the other pair of nip rolls 42a, 42b is V2, V1 and V2 can be set independently. In this embodiment, the peripheral speeds of the respective nip rolls are set so that V1 < V2. Thereby, the formed film is uniaxially stretched along the conveying direction, that is, the longitudinal direction, between the two pairs of nip rolls. Although not shown, another nip roll rotating at a peripheral speed V1' can be further installed between the nip rolls 41a, 41b and the nip rolls 42a, 42b, and the peripheral speeds of the respective nip rolls can be set so that V1 < V1' < V2, and stretching can be performed in two stages. Further, instead of using the above-mentioned roll stretching machine, a tenter stretching machine or a mandrel stretching machine may be used as the stretching section 40. Further, the stretching is not limited to the above-mentioned uniaxial stretching, and biaxial stretching may be performed depending on the type of the stretching machine.

[0014] The first heat treatment section 50 includes a first heat roll 51 and a second heat roll 52. The first and second heat rolls 51, 52 are arranged so that their rotation axes are parallel and their peripheral surfaces are spaced apart. Each of the heat rolls 51, 52 is provided with a heating means (not shown) and can be heated to an independent temperature.

[0015] The cooling section 60 includes a first chill roll 61 and a second chill roll 62. The first and second chill rolls 61, 62 are arranged so that their rotation axes are parallel and their peripheral surfaces are spaced apart. Each chill roll 61, 62 is provided with a cooling means (not shown) and can be cooled to an independent temperature.

[0016] The slit section 70 is equipped with a slit blade 71. The slit blade 71 is generally disk-shaped and is installed so that its surface is parallel to the film transport direction. One or more slit blades 71 are provided depending on the number of slits to be made in the film.

[0017] The second heat treatment section 80 is equipped with a heating means 81. As the heating means 81, a contact type heating means such as a heat roll as provided in the first heat treatment section 50, or a non-contact type heating means such as an infrared heater or a hot air blower can be used.

[0018] The winding section 90 is equipped with a winder 91. The film that has been transported through the second heat treatment section 80 is wound by the winder 91 into a roll.

[0019] The method for producing a film using the apparatus 10 having the above configuration will be described. First, the compound to be supplied to the hopper 21 contains a thermoplastic resin. In addition to the thermoplastic resin, the compound can contain other components depending on the specific use of the film. For example, when a porous film is produced as the film, the compound that is the raw material for the porous film can contain an inorganic filler in addition to the thermoplastic resin. The inorganic filler is used to generate a large number of openings in the target film. From the viewpoint of successfully generating openings, it is also advantageous for the compound to contain a metal soap together with the inorganic filler. Furthermore, if it is desired to impart water repellency to the target film, the compound may contain a triglyceride. Details of these components contained in the compound will be described later.

[0020] It is known that adding a metal soap to a compound increases the moisture permeability of the desired porous film (i.e., the number of micropores increases and the porosity increases). As a result, the moisture permeable film becomes flexible. Due to this, the porous film becomes more likely to be stretched during transportation, which increases the thermal shrinkage rate and makes it more likely to become tightly wound. In contrast, according to the manufacturing method of the present invention, a porous film in which thermal shrinkage is effectively suppressed can be obtained, so the present invention is particularly effective in manufacturing a porous film in which a metal soap is contained in a resin composition.

[0021] The compound supplied to the hopper 21 is heated and kneaded in the extruder 22 to become a molten resin. The molten resin is quantitatively discharged by the metering pump 23, passes through a filter 24, and is then extruded through a die 31 to be formed into a film 1a stretched in one direction. The film 1a in this state is an unstretched film. The unstretched film 1a is conveyed to the stretching section 40 after being shaped into a film by passing between the film-forming roll 32a and the nip roll 32b.

[0022] In the extension part 40, the unstretched film 1a undergoes stretching treatment while being conveyed. The stretching treatment is achieved by making the peripheral speed V2 of the pair of nip rolls 42a and 42b higher than the peripheral speed V1 of the pair of nip rolls 41a and 41b while gripping the unstretched film 1a with the pair of nip rolls 41a and 41b and gripping the unstretched film 1a with another pair of nip rolls 42a and 42b, thereby uniaxially stretching the unstretched film 1a along its conveyance direction (i.e., the longitudinal direction). As a result, the unstretched film 1a becomes the stretched film 1b. When an inorganic filler is contained in the unstretched film 1a, a large number of micropores are formed in the film by the stretching treatment. When a pair of nip rolls (not shown) rotating at a peripheral speed V1' is further installed between the nip rolls 41a and 41b and the nip rolls 42a and 42b, the stretching can be performed in two stages by setting the peripheral speeds of the respective nip rolls so that V1 < V1' < V2.

[0023] The stretching ratio of the unstretched film 1a in the stretching treatment may be appropriately set according to the intended use of the film and the like. For example, when manufacturing a porous film, it is preferable to stretch at a ratio of 1.1 times or more and 5.5 times or less in the uniaxial direction, whether the stretching is performed in one stage or two stages, from the viewpoint of successfully generating micropores. The stretching temperature of the unstretched film 1a depends on the type of thermoplastic resin. For example, when the thermoplastic resin contains a low melting point olefin resin described later, it is advantageous to set the stretching temperature preferably at 30°C or higher and 100°C or lower, more preferably at 35°C or higher and 95°C or lower, and even more preferably at 40°C or higher and 90°C or lower, from the viewpoint of being able to perform stretching successfully.

[0024] In the stretched film 1b obtained by the stretching process, the polymer chains of the resin constituting the film are oriented in the stretching direction (i.e., the conveying direction). Since the molecularly oriented state is a thermodynamically unstable state, it is preferable to relax the molecular orientation to make it a thermodynamically stable state from the viewpoint of the dimensional stability of the stretched film 1b. From this viewpoint, the stretched film 1b obtained by the stretching process is subjected to a heat treatment in the first heat treatment section 50 while being conveyed. The application of heat relaxes the molecular orientation of the polymer chains of the resin constituting the stretched film 1b, and crystallizes the molecular chains.

[0025] The degree of heating of the stretched film 1b in the first heat treatment section 50 may be appropriately selected according to the type of resin constituting the stretched film 1b. For example, when the resin constituting the stretched film 1b contains a low-melting point olefin resin described later, it is preferable to heat the stretched film 1b to preferably 50°C or higher from the viewpoint of reliable relaxation of molecular orientation. From this viewpoint, the stretched film 1b is heated to 60°C or higher, more preferably 70°C or higher. The upper limit of the heating temperature is preferably 130°C or lower from the viewpoint of preventing the stretched film 1b from melting. From this viewpoint, the stretched film 1b is heated to 125°C or lower, more preferably 120°C or lower. In summary, when the resin constituting the stretched film 1b contains a low-melting point olefin resin described later, the degree of heating of the stretched film 1b is preferably 50°C or higher and 130°C or lower, more preferably 60°C or higher and 125°C or lower, and more preferably 70°C or higher and 120°C or lower. The heating temperature of the stretched film 1b in the first heat treatment section 50 refers to the temperature of the peripheral surfaces of the first and second heat rolls 51, 52. When the peripheral surfaces of the first and second heat rolls 51, 52 have different temperatures, the heating temperature refers to the higher temperature.

[0026] The heat treatment in the first heat treatment section 50 is preferably performed at a temperature higher than the temperature of the stretching treatment in the stretching section 40. This can reliably relax the orientation generated in the polymer chains of the film 1b. The difference between the heating temperature T2 in the first heat treatment section 50 and the stretching temperature T1 in the stretching section 40 is preferably 5° C. to 70° C., more preferably 10° C. to 60° C., and even more preferably 15° C. to 50° C., provided that T2>T1. By performing heat treatment under such temperature relationship, the orientation of the polymer chains in the film 1b can be reliably relaxed.

[0027] The relaxation of the orientation of the polymer chains of the stretched film 1b by heating is accompanied by shrinkage of the film 1b in the stretching direction (i.e., the conveying direction). Therefore, from the viewpoint of reliably relaxing the orientation of the polymer chains, it is preferable to make the conveying speed of the stretched film 1b in the first heat-treating section 50 lower than the conveying speed of the stretched film 1b in the stretching section 40. This weakens the force pulling the film in the conveying direction in the first heat-treating section 50, and promotes the shrinkage of the stretched film 1b by the first heat-treating section 50. In other words, the film 1b can be shrunk in the conveying direction while being subjected to heat treatment. However, if the conveying speed of the stretched film 1b in the first heat-treating section 50 is made too low, the film will slacken and wind around the roll. From this viewpoint, when the conveying speed of the stretched film 1b in the stretching section 40 is V2 and the conveying speed of the stretched film 1b in the first heat treatment section 50 is V3, it is advantageous to set V2 / V3 to preferably 0.40 to 0.95, more preferably 0.45 to 0.92, and even more preferably 0.50 to 0.90. It is preferable to set the shrinkage percentage of the stretched film 1b when heat-treated with this speed relationship to preferably 5% to 60%, more preferably 8% to 55%, and even more preferably 10% to 50%.

[0028] The stretched film 1b, whose molecular orientation has been relaxed by heating in the first heat treatment section 50, is then transported to the cooling section 60, where it is cooled while being transported. The cooling process of the stretched film 1b is performed for the purpose of fixing the state in which the molecular orientation has been relaxed. Therefore, the degree of cooling of the stretched film 1b in the cooling section 60 may be appropriately selected according to the type of resin constituting the stretched film 1b. For example, when the resin constituting the stretched film 1b includes a low-melting-point olefin resin described later, it is preferable to cool the stretched film 1b to preferably 50°C or less from the viewpoint of reliably fixing the relaxation of the molecular orientation. From this viewpoint, the stretched film 1b is more preferably cooled to 45°C or less, and even more preferably 40°C or less. It is preferable that the lower limit of the cooling temperature is 0°C or more from the viewpoint of economic efficiency. From this viewpoint, the stretched film 1b is more preferably cooled to 5°C or more, and even more preferably 10°C or more. In summary, when the resin constituting the stretched film 1b is a low-melting point olefin resin described below, the degree of cooling of the stretched film 1b is preferably from 0° C. to 50° C., more preferably from 5° C. to 45° C., and even more preferably from 10° C. to 40° C. The cooling temperature of the stretched film 1b in the cooling section 60 refers to the temperature of the circumferential surfaces of the first and second chill rolls 61, 62. When the temperatures of the circumferential surfaces of the first and second chill rolls 61, 62 are different, the cooling temperature refers to the lower temperature.

[0029] The stretched film 1b, whose molecular orientation has been relaxed and fixed, is then transported to the slitting section 70, where it is slit into a plurality of strips while being transported. The slit stretched film 1b is taken up by a winder 91 in a take-up section 90.

[0030] In this embodiment, immediately before the heat-treated stretched film 1b is wound up, the film 1b is subjected to a second heat treatment in the second heat treatment section 80. The purpose of the second heat treatment is as follows. A predetermined tension is repeatedly applied to the film 1b being transported before it is wound by the winder 91. In this case, depending on the type of resin constituting the film, the polymer chains are oriented again due to the tension of the transport, and the film 1b is wound by the winder while still in the molecular orientation state. In addition, tension is also applied to the film 1b during the slitting process, so that the polymer chains are also likely to be oriented due to this. In particular, when the film 1b contains a low-melting-point olefin resin described later, the film 1b is easily deformed even with a small tension, and when the film 1b is deformed, the polymer chains are oriented, so this phenomenon is likely to occur. The molecular orientation of the film 1b while still in the molecular orientation state is gradually relaxed over time. As a result, the film 1b shrinks along the stretching direction (i.e., the transport direction), and the dimensional stability is reduced. When the film 1b is in a wound state, the film 1b is tightened. When the film 1b is incorporated into an article, the article is warped. In order to suppress the occurrence of such shrinkage, in this embodiment, a second heat treatment is performed in the second heat treatment section 80 to relax the orientation of the polymer chains caused by the tension during transport. For this purpose, it is advantageous to perform the second heat treatment just before winding up the film 1b. In other words, it is advantageous to position the second heat treatment section 80 just before the winding section 90. This is because if there is a distance between the second heat treatment section 80 and the winding section 90, the polymer chains of the film 1b may be oriented again between them due to the tension during transport. "Just before the winding section 90" refers to a position closer to the winding section 90 than half the length of the film transported from the first heat treatment section 50 to the winding section 90 (i.e., the length of the film transport path). From the viewpoint of alleviating the orientation of polymer chains caused by the tension during transport, a position closer to the winding section 90 than the slit section 70 is preferable.

[0031] The first heat treatment performed in the first heat treatment section 50 and the second heat treatment performed in the second heat treatment section 80 are distinguished by the presence of one or more processes other than heat treatment between the two heat treatments. Examples of such processes include the cooling process and slitting process described above. Therefore, when heat treatments are performed consecutively without any processes other than heat treatment (for example, when the stretched film 1b is brought into contact with a plurality of heat rolls 51, 52 consecutively as shown in FIG. 1), the series of heat treatments is regarded as a single heat treatment.

[0032] The second heat treatment in the second heat treatment section 80 can be performed using contact heating means using heat rolls 51, 52 as provided in the first heat treatment section 50. Alternatively, non-contact heating means such as an infrared heater or a hot air blower can be used. Of these heating means, the use of non-contact heating means is preferable because it does not interfere with the transport of the film 1b or the take-up of the film 1b in the take-up section 90 located immediately after the second heat treatment section 80 even if the film 1b is heated and slightly softened to become sticky.

[0033] The second heat treatment in the second heat treatment section 80 is preferably performed at a temperature higher than the temperature of the stretching treatment in the stretching section 40. This can reliably relax the re-orientation generated in the polymer chains of the film 1b. The degree of heating of the film 1b in the second heat treatment section 80 is preferably higher than the stretching temperature in the stretching section 40. For example, when the resin constituting the film 1b contains a low melting point olefin resin described later, it is preferable to heat the stretched film 1b to 50°C or higher from the viewpoint of reliably relaxing the molecular orientation. From this viewpoint, it is more preferable that the heating of the film 1b is 60°C or higher, and even more preferably 70°C or higher. The upper limit of the heating temperature is preferably 130°C or lower from the viewpoint of preventing the film 1b from melting. From this viewpoint, it is more preferable that the heating of the film 1b is 125°C or lower, and even more preferably 120°C or lower. Summarizing the above, when the resin constituting the film 1b contains a low melting point olefin resin described later, the degree of heating of the film 1b in the second heat treatment section 80 is preferably 50°C or higher and 130°C or lower, more preferably 60°C or higher and 125°C or lower, and even more preferably 70°C or higher and 120°C or lower.

[0034] The difference between the heating temperature T3 by the second heat treatment section 80 and the stretching temperature T1 in the stretching section 40 is preferably 5°C or higher and 70°C or lower, more preferably 10°C or higher and 60°C or lower, and even more preferably 15°C or higher and 50°C or lower on the condition that T3>T1. By performing the heat treatment with such a temperature relationship, the orientation of the polymer chains in the film 1b can be reliably relaxed. Note that the heating temperature T2 by the first heat treatment section 50 and the heating temperature T3 by the second heat treatment section 80 may be such that T2>T3, T2<T3, or T2=T3. In order to reliably relax the orientation of the polymer chains, it is preferable that T2<T3.

[0035] As with the heating of the stretched film 1b in the first heat-treating section 50, the relaxation of the orientation of the polymer chains by the second heating of the stretched film 1b in the second heat-treating section 80 also involves shrinkage of the film 1b in the stretching direction (i.e., the conveying direction). Therefore, from the viewpoint of ensuring relaxation of the orientation of the polymer chains, it is preferable to set the winding speed of the stretched film 1b in the winding section 90 lower than the conveying speed of the stretched film 1b in the first heat-treating section 50. This reduces the tension acting on the film between the winding section 90 and the first heat-treating section 50, and promotes the shrinkage of the stretched film 1b in the second heat-treating section 80. In other words, the film 1b can be shrunk in the conveying direction while undergoing the second heat treatment. If the winding speed is too low, the film will slacken and the winding will become unstable. When the winding becomes unstable, there is a concern that the film may meander during winding, causing the film to collapse, or the film may be wound around the winding shaft. From these viewpoints, when the take-up speed of the stretched film 1b in the take-up section 90 is V4 and the conveying speed of the stretched film 1b in the first heat treatment section 50 is V3, it is advantageous to set V3 / V4 preferably to 0.8 to 0.99, more preferably to 0.85 to 0.98, and even more preferably to 0.90 to 0.97. It is preferable to set the shrinkage percentage of the stretched film 1b when heat-treated at this speed relationship to preferably 1% to 20%, more preferably 2% to 15%, and even more preferably 3% to 10%.

[0036] The film 1b obtained in this manner has a relaxed orientation of the polymer chains, so that it is less likely to shrink and has excellent dimensional stability. Specifically, the film 1b has a high dimensional stability with a heat shrinkage rate in the machine direction of preferably 8% or less, more preferably 6% or less. The method for measuring the heat shrinkage rate will be described in the examples below.

[0037] Next, the compound used in the manufacturing method of the present invention will be described. The compound preferably contains a thermoplastic resin composition, particularly an olefin-based resin composition. In this specification, the term "thermoplastic resin composition" refers to a composition that is composed only of various thermoplastic resins and does not contain any components other than resins. The "olefin resin composition" includes both the case where only one type of various olefin resins is contained and the case where two or more types are contained. In addition, the "olefin resin composition" is a concept that consists only of various olefin resins and does not contain other resins or components other than resins. It is not prohibited for the compound to contain a thermoplastic resin other than the olefin resin composition.

[0038] The thermoplastic resin contained in the compound is selected from appropriate resins depending on the specific application of the film, such as, but not limited to, olefin resins, polyester resins, acrylic resins, and vinyl chloride resins. Examples of the olefin resin that can be used include polyethylene resin, polypropylene resin, ethylene-α-olefin copolymer resin, etc. Examples of the polyethylene resin that can be used include low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), branched low-density polyethylene (LDPE), and high-density polyethylene (HDPE).

[0039] In the case where it is desired to impart flexibility to the target film, it is preferable that the compound contains an olefin-based resin composition, and that the olefin-based resin composition contains a low-melting-point olefin-based resin as the olefin-based resin. The low-melting-point olefin-based resin is preferably a copolymer of ethylene and an α-olefin. Examples of the α-olefin include propylene, 1-butene, 1-pentene, and 1-hexene.

[0040] From the viewpoint of imparting flexibility to the film, the low melting point olefin resin preferably has a melting point of less than 90°C, more preferably less than 80°C, and even more preferably less than 70°C. Similarly, from the viewpoint of imparting flexibility to the film, the low melting point olefin resin has a density of 0.895 g / cm3 It is preferable that the density is 0.885 g / cm or less. 3 More preferably, it is 0.875 g / cm or less. 3 It is even more preferable that: The low melting point olefin resin preferably has a density of 0.840 g / cm 3 If the density is equal to or greater than 0.850 g / cm3, blocking is unlikely to occur in the target film. 3 More preferably, it is 0.860 g / cm or more. 3 More preferably, the above is true. In summary, the density of low-melting-point olefin resin is 0.840 g / cm 3 More than 0.895g / cm 3 It is preferable that the density is 0.850 g / cm or less. 3 More than 0.885g / cm 3 More preferably, it is 0.860 g / cm or less. 3 More than 0.875g / cm 3 It is even more preferable that: The above densities are values ​​at 25° C. In the following description, "density" refers to the value measured at this temperature.

[0041] The olefin resin composition preferably contains 30 parts by mass or more of the above-mentioned low melting point olefin resin in 100 parts by mass of the olefin resin composition, from the viewpoint of imparting a satisfactory flexibility to the intended film. From the viewpoint of making this advantage more prominent, the low melting point olefin resin is more preferably contained in 100 parts by mass of the olefin resin composition in an amount of 33 parts by mass or more, and even more preferably contained in 100 parts by mass of the olefin resin composition in an amount of 35 parts by mass or more. In addition, the olefin resin composition preferably contains 95 parts by mass or less of the above-mentioned low melting point olefin resin in 100 parts by mass of the olefin resin composition, since blocking is unlikely to occur in the target film. From the viewpoint of making this advantage more prominent, the low melting point olefin resin is more preferably contained in 100 parts by mass of the olefin resin composition in an amount of 92 parts by mass or less, and even more preferably contained in 90 parts by mass or less. Taking all of the above into consideration, the olefin-based resin composition preferably contains 30 parts by mass or more and 95 parts by mass or less of the above-mentioned low melting point olefin-based resin per 100 parts by mass of the olefin-based resin composition, more preferably 33 parts by mass or more and 92 parts by mass or less, and even more preferably 35 parts by mass or more and 90 parts by mass or less.

[0042] If the olefin resin composition contains a high melting point olefin resin in addition to the above-mentioned low melting point olefin resin, the high melting point olefin resin is preferably crystallized in heat treatment, and heat shrinkage can be reduced.In particular, in order to realize high speed molding of the porous film to be melt-molded, from the viewpoint of realizing solidification in a short time, the high melting point olefin resin preferably has a melting point of 95°C or more, more preferably 100°C or more, and even more preferably 110°C or more.

[0043] From the viewpoint of achieving both flexibility and thermal shrinkage of the film, it is preferable that the high melting point olefin resin has a relatively low density, specifically, 0.950 g / cm 3 It is preferable that the density is 0.940 g / cm or less. 3 More preferably, it is 0.930 g / cm or less. 3 It is even more preferable that: In order to prevent blocking, the density of the high melting point olefin resin is set to 0.900 g / cm. 3 It is preferable that the content is 0.905 g / cm or more. 3 More preferably, it is 0.910 g / cm or more. 3 More preferably, the above is true. In summary, the density of high melting point olefin resin is 0.900g / cm 3 More than 0.950g / cm 3 It is preferable that the density is 0.905 g / cm or less. 3 More than 0.940g / cm 3 More preferably, it is 0.910 g / cm or less. 3 More than 0.930g / cm 3 It is even more preferable that: As the high melting point olefin resin having the above density, it is preferable to use polyethylene such as low density polyethylene or linear low density polyethylene, and it is particularly preferable to use linear low density polyethylene because crystallization by heat treatment is promoted. In particular, linear low density polyethylene polymerized by a metallocene catalyst is more preferable because crystallization by heat treatment is promoted.

[0044] The metallocene catalyst is a combination of a metallocene, which is a compound having a structure in which a transition metal such as titanium, zirconium, or hafnium is sandwiched between unsaturated cyclic compounds containing a π-electron system cyclopentadienyl group or a substituted cyclopentadienyl group, and a cocatalyst such as an aluminum compound. Examples of the metallocene include titanocene and zirconocene. Examples of the aluminum compound include alkylaluminoxane, alkylaluminum, aluminum halide, and alkylaluminum halide.

[0045] The olefin resin composition preferably contains 5 parts by mass or more of the high melting point olefin resin having the above-mentioned density in 100 parts by mass of the olefin resin composition, because the high melting point olefin resin is crystallized by heat treatment and the thermal shrinkage rate can be reduced. From the viewpoint of making this advantage more prominent, the high melting point olefin resin is more preferably contained in 8 parts by mass or more, and even more preferably contained in 100 parts by mass of the olefin resin composition. In addition, the olefin resin composition used in the present invention preferably contains the above-mentioned high melting point olefin resin in an amount of 70 parts by mass or less per 100 parts by mass of the olefin resin composition, from the viewpoint of compatibility with the flexibility of the porous film. In order to make this advantage more prominent, the high melting point olefin resin is more preferably contained in an amount of 65 parts by mass or less, and even more preferably contained in an amount of 60 parts by mass or less per 100 parts by mass of the olefin resin composition. Taking all of the above into consideration, the olefin resin composition used in the present invention preferably contains 5 parts by mass or more and 70 parts by mass or less of a high melting point olefin resin having the above-mentioned density per 100 parts by mass of the olefin resin composition, more preferably 8 parts by mass or more and 65 parts by mass or less, and even more preferably 10 parts by mass or more and 60 parts by mass or less.

[0046] The olefin resin composition used in the present invention has a density of 0.900 g / cm 3 Preferably, it is less than 0.895 g / cm 3 More preferably, it is 0.885 g / cm or less. 3 It is even more preferable that: The olefin resin composition preferably has a density of 0.840 g / cm 3 If the density of the olefin resin composition is 0.850 g / cm or more, blocking is unlikely to occur in the film. 3 More preferably, it is 0.860 g / cm or more. 3 More preferably, the above is true. In summary, the olefin resin composition has a density of 0.840 g / cm 3 More than 0.900g / cm 3 Preferably, it is less than 0.850 g / cm 3 More than 0.895g / cm 3 More preferably, it is 0.860 g / cm or less. 3 More than 0.885g / cm 3 It is even more preferable that:

[0047] The inorganic filler contained in the compound is used when a porous film is to be produced as the target film. The inorganic filler is a substance that causes peeling at the interface with the thermoplastic resin to form micropores. From this viewpoint, the inorganic filler has an average particle diameter D 50 The average particle diameter D of the inorganic filler is preferably 30 μm or less, more preferably 10 μm or less, and is preferably 0.5 μm or more, and even more preferably 1.0 μm or more. 50refers to the weight cumulative particle size at a cumulative weight of 50% by mass as measured by a laser diffraction / scattering particle size distribution measurement method.

[0048] Examples of inorganic fillers include calcium carbonate, gypsum, talc, clay, kaolin, silica, diatomaceous earth, magnesium carbonate, barium carbonate, magnesium sulfate, barium sulfate, calcium phosphate, aluminum hydroxide, zinc oxide, titanium oxide, alumina, mica, zeolite, carbon black, and mixtures thereof. In particular, it is preferable to use calcium carbonate because it is easy to adjust the particle size to the above-mentioned range.

[0049] The inorganic filler is preferably contained in an amount of 50 parts by mass or more per 100 parts by mass of the thermoplastic resin composition, particularly per 100 parts by mass of the olefin-based resin composition, in order to form a sufficient amount of fine pores and sufficiently increase the moisture permeability of the porous film, more preferably 60 parts by mass or more, and even more preferably 80 parts by mass or more. In addition, the inorganic filler is preferably contained in an amount of 400 parts by mass or less per 100 parts by mass of the thermoplastic resin composition, particularly per 100 parts by mass of the olefin-based resin composition, from the viewpoint of sufficiently enhancing the leakproofness of the porous film, more preferably 350 parts by mass or less, and even more preferably 200 parts by mass or less.

[0050] When an inorganic filler is blended in a compound to produce a porous film, it is preferable to blend a metal soap in addition to the inorganic filler in order to successfully form micropores. The metal soap is used for the purpose of smoothly stretching the resin film formed from the compound to generate micropores. In particular, when an olefin-based resin composition containing a low-melting-point olefin-based resin is used as the thermoplastic resin composition, flexibility is imparted to the intended film, while interfacial peeling between the film and the inorganic filler is unlikely to occur during film stretching. Therefore, when an olefin-based resin composition containing a low-melting-point olefin-based resin is used, it is particularly advantageous to use a metal soap in order to promote interfacial peeling between the olefin-based resin composition and the inorganic filler.

[0051] As the metal soap, metal salts of fatty acids are preferably used. Examples of fatty acids include caprylic acid, palmitic acid, stearic acid, capric acid, oleic acid, myristic acid, lauric acid, etc. Examples of metal salts include calcium, aluminum, magnesium, zinc, etc. salts of these fatty acids. Fatty acids themselves are known as substances similar to metal salts of fatty acids and are incorporated into porous films. Fatty acids are used to enhance the dispersibility of inorganic fillers. In other words, fatty acids are dispersants. However, fatty acids do not have the function of promoting interfacial peeling between a thermoplastic resin composition and an inorganic filler. Therefore, in the present invention, fatty acid metal salts and fatty acids are clearly distinguished from each other in terms of material and function.

[0052] The metal soap is preferably contained in an amount of 0.5 parts by mass or more per 100 parts by mass of the inorganic filler, from the viewpoint of successfully generating micropores. From the viewpoint of making this advantage more prominent, the metal soap is preferably contained in an amount of 1.5 parts by mass or more, and more preferably 2.0 parts by mass or more per 100 parts by mass of the inorganic filler. In order to maintain good moldability, the metal soap is preferably contained in an amount of 15 parts by mass or less per 100 parts by mass of the inorganic filler. In order to make this advantage more pronounced, the metal soap is preferably contained in an amount of 10 parts by mass or less, and more preferably 8 parts by mass or less, per 100 parts by mass of the inorganic filler. Taking all of the above into consideration, the metal soap is preferably contained in an amount of 0.5 parts by mass or more and 15 parts by mass or less, more preferably 1.5 parts by mass or more and 10 parts by mass or less, and even more preferably 2.0 parts by mass or more and 8 parts by mass or less, per 100 parts by mass of the inorganic filler.

[0053] The metal soap is preferably contained in an amount of 0.5 parts by mass or more per 100 parts by mass of the thermoplastic resin composition, from the viewpoint of successfully generating micropores. From the viewpoint of making this advantage more prominent, the metal soap is more preferably contained in an amount of 1.0 part by mass or more, and even more preferably contained in an amount of 2.0 parts by mass or more per 100 parts by mass of the thermoplastic resin composition. In order to maintain good moldability, the metal soap is preferably contained in an amount of 20 parts by mass or less per 100 parts by mass of the thermoplastic resin composition. In order to make this advantage more pronounced, the metal soap is preferably contained in an amount of 15 parts by mass or less, and even more preferably 10 parts by mass or less, per 100 parts by mass of the thermoplastic resin composition. Taking all of the above into consideration, the metal soap is preferably contained in an amount of 0.5 to 20 parts by mass, more preferably 1.0 to 15 parts by mass, and even more preferably 2.0 to 10 parts by mass, per 100 parts by mass of the thermoplastic resin composition.

[0054] In relation to the above-mentioned olefin resin composition, it is preferable to use a metal soap having a precipitation temperature higher than the solidification temperature of the olefin resin composition, from the viewpoint of successfully forming micropores and obtaining a moisture-permeable film having high moisture permeability and high water resistance. In detail, when the precipitation temperature of the metal soap is higher than the solidification temperature of the olefin resin composition, the metal soap precipitates earlier than the olefin resin composition solidifies, and the metal soap can smoothly migrate to the surface of the inorganic filler. As a result, the releasability between the inorganic filler and the olefin resin composition during stretching is improved, and micropores are smoothly formed. In order to make this advantage more prominent, when the precipitation temperature of the metal soap is Ts (°C) and the solidification temperature of the olefin resin composition is Tp (°C), the value of Ts-Tp is preferably greater than 0°C, more preferably 1°C or more, and even more preferably 2°C or more. In addition, the value of Ts-Tp is preferably 50°C or less.

[0055] Provided that the value of Ts-Tp is within the aforementioned range, the precipitation temperature Ts of the metal soap is preferably 80°C or higher and 180°C or lower, more preferably 90°C or higher and 170°C or lower, and even more preferably 100°C or higher and 160°C or lower. On the other hand, the solidification temperature Tp of the olefin resin composition is preferably 60°C or more and 130°C or less, more preferably 70°C or more and 120°C or less, and even more preferably 80°C or more and 115°C or less, provided that the value of Ts-Tp is within the above-mentioned range.

[0056] The precipitation temperature Ts of the metal soap is measured using a hot stirrer and a thermocouple as follows. Using a hot stirrer, 0.43 g of the metal soap is added to 5.0 g of paraffin oil, and the mixture is heated while stirring until the metal soap dissolves. After stopping stirring the liquid with the stirrer, the temperature of the paraffin oil is lowered at a rate of 0.2°C / min, and the temperature of the paraffin oil when the metal soap begins to precipitate is read with a thermocouple, and this temperature is defined as the precipitation temperature of the metal soap. Note that if the metal soap does not dissolve in the paraffin oil despite the paraffin oil being heated to 210°C, the precipitation temperature is defined as 210°C. On the other hand, the solidification temperature Tp of the olefin resin composition is measured by the following method in accordance with JIS K 7121 (method of determining extrapolated crystallization end temperature). Using a moisture-permeable film of about 2.0 mg as a sample, differential scanning calorimetry (DSC) is performed using a differential scanning calorimeter (DSC7000X, manufactured by Hitachi High-Tech Science Co., Ltd.) under the conditions of a measurement temperature range of 30°C to 260°C, a heating rate of 10°C / min, a heating rate of 50°C / min, an air environment, and a data sampling period of 0.5 s. In the temperature drop process of the obtained DSC curve, an exothermic peak that occurs when the olefin resin composition solidifies (crystallizes) is observed. The solidification temperature of the olefin resin composition is the temperature at the intersection of a straight line extending the baseline on the lower side of the peak temperature to the higher side for the peak with the highest heat generation during the temperature drop process, and an approximation straight line drawn between the data of the two points where the slope of the curve on the lower side of the peak is maximum. When two or more overlapping exothermic peaks exist, for example, the software PeakFit v4.12 (manufactured by Hulinks Corporation) is used to separate the peaks, and then the solidification temperature is determined by the above-mentioned method.

[0057] A water repellent can be added to the compound. This can impart water repellency to the target film. In particular, when the target film is a porous film, that is, a film that is permeable to steam but has a low permeability to water (liquid water), adding a water repellent to the compound is preferable because it makes the porous film even more resistant to water permeation.

[0058] As the water repellent, it is preferable to use a triglyceride. By using a triglyceride, the leakproofness of the porous film is increased. In particular, it is preferable to use a triglyceride that contains a group derived from a fatty acid having 16 to 22 carbon atoms, and the group is a hydrocarbon group that does not have an unsaturated bond or a substituent. By using such a triglyceride, the leakproofness of the porous film containing the triglyceride is increased more than ever before.

[0059] In order to make the above-mentioned advantages more pronounced, the amount of triglyceride blended into the compound is preferably 0.1 part by mass or more, more preferably 0.5 part by mass or more, and even more preferably 1.0 part by mass or more, per 100 parts by mass of the thermoplastic resin composition, particularly per 100 parts by mass of the olefin-based resin composition. From the viewpoint of film formability, the amount of triglyceride is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and even more preferably 20 parts by mass or less, per 100 parts by mass of the thermoplastic resin composition, particularly per 100 parts by mass of the olefin-based resin composition. Taking all of the above into consideration, the amount of triglyceride to be blended is preferably 0.1 parts by mass or more and 30 parts by mass or less, more preferably 0.5 parts by mass or more and 25 parts by mass or less, and even more preferably 1.0 parts by mass or more and 20 parts by mass or less, per 100 parts by mass of the thermoplastic resin composition, particularly per 100 parts by mass of the olefin-based resin composition.

[0060] The film produced by the method of the present invention using the compound as described above is preferably a porous moisture-permeable film, and the film preferably contains 50 parts by mass or more and 400 parts by mass or less of an inorganic filler per 100 parts by mass of the olefin resin composition. In this case, the olefin resin composition has a density of 0.840 g / cm. 3 More than 0.900g / cm 3 The olefin resin composition preferably contains a low melting point olefin resin having a melting point of less than 90° C. Furthermore, the olefin resin composition preferably contains a low melting point olefin resin having a density of 0.840 g / cm 3 More than 0.895g / cm 3 From the viewpoint of imparting flexibility to the film, it is preferable that the olefin resin composition contains 30 parts by mass or more and 95 parts by mass or less of a low melting point olefin resin having a melting point of 100 parts by mass or less. When the degree of flexibility of the film is expressed as the degree of flexibility deformation, the degree of flexibility deformation in the machine direction is preferably 0.060 N / (mm (g / m 2)) or less, and more preferably 0.057 N / (mm (g / m 2 ) or less, more preferably 0.055 N / (mm (g / m 2 The lower limit of the degree of flexible deformation is 0.005 N / (mm (g / m) from the viewpoint of maintaining the strength of the film. 2 It is preferable that the heat shrinkage rate in the machine direction of the film produced by the method of the present invention is 8% or less, particularly 6% or less, as described above.

[0061] Although the present invention has been described above based on its preferred embodiment, the present invention is not limited to the above embodiment. For example, in the device 10 shown in Fig. 1, the slit section 70 is provided upstream of the second heat treatment section 80, but the slit section 70 does not need to be provided. Instead, if necessary, the wound film may be unwound in a separate process and the unwound film may be slit. In addition, in the embodiment 10 shown in FIG. 1, a cooling section 60 is provided between the first heat treatment section 50 and the second heat treatment section 80. However, depending on the type of thermoplastic resin used, etc., it may not be necessary to provide a cooling section 60, and the film heated in the first heat treatment section 50 may be allowed to cool naturally. EXAMPLES

[0062] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to such examples. Unless otherwise specified, "%" means "% by mass".

[0063] [Examples 1 to 5 and Comparative Example 1] The components shown in Table 1 below were weighed out in the amounts shown in the table. These were mixed in a Henschel mixer (Kawata Co., Ltd.). The resulting mixture was kneaded in a twin-screw extruder (Toyo Seiki Co., Ltd.) at a set temperature of 180°C and a screw rotation speed of 180 rpm to obtain a pelletized compound. The units of the compositions in Table 1 are parts by mass. Using this compound, a porous film was produced using the device 10 shown in Figure 1. (2) Film production A film was formed from the molten compound using a 150 mm wide T-die (manufactured by Toyo Seiki Co., Ltd.) The temperature of the T-die was set at 200°C. (3) Film manufacturing The unstretched film was stretched uniaxially to obtain a porous stretched film. The stretching temperature was set to 60° C., and the stretch ratio was set to 2.5 times. (4) First heat treatment The stretched film was heat-treated using two heat rolls. The peripheral temperature T2 of the heat rolls was set to the value shown in Table 2. In addition, the peripheral speed V2 of the rolls in the stretching section relative to the peripheral speed V3 of the heat rolls was set to the value shown in Table 2. (5) Cooling treatment The stretched film was cooled using two chill rolls. The peripheral temperatures of the chill rolls were set to the values ​​shown in Table 2. (6) Slit The stretched film was slit into multiple strips. (7) Second heat treatment The stretched film was heat-treated using an infrared heater. The heat treatment was performed so that the surface temperature T3 of the film became the value shown in Table 2. The second heat treatment was performed immediately before winding. (8) Winding The ratio of the transport speed V3 of the stretched film in the first heat treatment section to the winding speed (circumferential speed) V4 was set to the values ​​shown in Table 2, and winding was performed.

[0064] 〔evaluation〕 The heat shrinkage and flexibility of the films obtained in the examples and comparative examples were measured by the following methods. The results are shown in Table 1.

[0065] [Heat shrinkage rate] The porous film was cut into three pieces of 60 mm wide and 100 mm long to obtain three test pieces. The obtained test pieces were stored in an environment of 50° C. for one day. The length L1 of the porous film after storage was measured, and the value of (100-L1) was calculated, and the average value of these values ​​was taken as the thermal shrinkage rate of the porous film.

[0066] [Flexibility] The porous film was cut into three pieces of test specimens, each 150 mm in the machine direction and 30 mm in the width direction. The test specimens were fixed to a tensile tester (product name: AG-1S, manufactured by Shimadzu Corporation) so that the initial length L0 of the test specimen was 100 mm. After fixing, the load read by the tensile tester was set to zero, and the test specimen was extended to a length 1.3 times L0 at a deformation rate of 200 mm / min, and then immediately contracted to L0 at a deformation rate of 200 mm / min to perform a cycle test. From the obtained data, the load (F) at the time of 1.03-fold deformation during the extension process was calculated. 3% ) and calculate the degree of flexible deformation (N / (mm (g / m 2 The average value of the three test pieces was taken as the degree of flexible deformation of the porous film. Degree of flexibility (N / (mm (g / m 2 )))=F 3% (N) / (0.03×30(mm)×film basis weight(g / m 2 ))

[0067] [Table 1]

[0068] [Table 2]

[0069] As is clear from the results shown in Table 2, the porous films obtained in the respective Examples have a small heat shrinkage rate, indicating that the orientation of the polymer chains is relaxed. In contrast, the porous film obtained in Comparative Example 1 has a larger heat shrinkage rate than the Examples, indicating that the relaxation of the orientation of the polymer chains is insufficient. It is also clear that the porous films obtained in the respective Examples have higher flexibility than the porous film obtained in Comparative Example 1. [Explanation of symbols]

[0070] 10 Manufacturing equipment 20 Melt kneading section 30 Molding section 40 Stretching section 50 First heat treatment section 60 Cooling section 70 Slit section 80 Second heat treatment section 90 Winding section

Claims

1. The molten resin is extruded through a die to form a film that stretches in one direction. The film obtained by the film formation is stretched in the longitudinal direction while being transported, The stretched film is subjected to a first heat treatment while being transported; A film manufacturing method comprising a step of winding up the heat-treated film, The method for producing a film further comprises subjecting the heat-treated film to a second heat treatment immediately before winding the film.

2. The method according to claim 1 , wherein the film is shrunk in the machine direction while being subjected to the second heat treatment.

3. The method according to claim 1 , wherein the second heat treatment is carried out at a temperature higher than the drawing temperature.

4. The method according to claim 3, wherein a difference between a heating temperature T2 in the first heat treatment and a temperature T1 in the stretching is 5° C. or more and 70° C. or less, provided that T2>T1.

5. The method according to claim 1 , wherein the second heat treatment is performed in a non-contact manner.

6. The method according to claim 1 , wherein the molten resin contains 50 parts by mass or more and 400 parts by mass or less of an inorganic filler based on 100 parts by mass of the olefin-based resin composition.

7. The method according to claim 6 , wherein the olefin resin composition contains a low-melting-point olefin resin having a melting point of less than 90° C.

8. The method according to claim 6 or 7, wherein the molten resin contains, relative to 100 parts by mass of the inorganic filler, 0.5 parts by mass to 15 parts by mass of a metal soap and 0.5 parts by mass to 5 parts by mass of a fatty acid.

9. The method according to claim 8, wherein the value of Ts-Tp is greater than 0°C, where Ts (°C) is the deposition temperature of the metal soap and Tp (°C) is the solidification temperature of the olefin resin composition.

10. The method according to claim 6 or 7, wherein the molten resin contains 0.1 parts by mass or more and 30 parts by mass or less of triglyceride per 100 parts by mass of the olefin-based resin composition.

11. The olefin resin composition has a density of 0.840 g / cm 3 0.900g / cm or more 3 The method according to claim 6 or 7, wherein the amount of the reaction is less than 100%.

12. The composition contains an inorganic filler in an amount of 50 parts by mass or more and 400 parts by mass or less relative to 100 parts by mass of the olefin-based resin composition, The olefin resin composition contains a low-melting-point olefin resin having a melting point of less than 90° C. The degree of deformation in the machine direction is 0.060 N / (mm·(g / m 2 )) is less than or equal to A porous film having a heat shrinkage rate in the machine direction of 8% or less.

13. The olefin resin composition has a density of 0.840 g / cm 3 0.900g / cm or more 3 The porous film of claim 12, wherein the porous film has a thickness of less than 1 / 2 mm.